Enhanced virtual learning using Google Education & Padlet as a tool for inquiry-based learning for the speciation topic / Nashimah Banu Habeeb Mohamed - Habeeb Mohamed, Nashimah Banu (Faculty of Computer and Mathematical Sciences, 2021)
Active teaching and learning implementation as well as full involvement by students is particularly challenging on learning during the COVID-19 Pandemic. Therefore, the study conducted aims to examine the effectiveness of applying inquiry based learning for topic of Speciation in Biology with the integration of technology via virtual learning. In this study, the 5E model of Inquiry- based was adapted by integrating Google education technology and Padlet while teaching and learning was conducted virtually. A total of 42 Biology SB025 (matriculation) students were involved in the implementation of this learning. Data collection is carried by students answering a questionnaire method with Likert scale. Two forms of constructs are provided, namely Virtual Learning Effectiveness with the help of Google & Padlet and Learning Effectiveness and comprehension by inquiry with the help of Google & Padlet. The findings from both constructs showed overall mean result is 4.716 and 4.86 which the level of application for this construct is high. This demonstrates the ability to master an active involvement of students in learning virtually and helps students to be more engaged and student centered. This shows a good level of understanding of students with inquiry-based learning with the help of google education and Padlet as a medium of sharing and collaboration between researchers with students and students among themselves. In conclusion, inquiry-based learning with the application of technology can make teaching and learning more effective and maximize student involvement in virtual learning.